Strategi Kampanye Partai Amanat Nasional Pada Pemilu Legislatif 2024: Pendekatan Teori Marketing-Mix - Wiwid (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2024)
This article examines to find out the successful campaign strategy of the National Mandate Party (Partai Amanat Nasional, PAN) in increasing its vote in the 2024 Legislative Election. Methodologically, this article uses qualitative method by applying case study approach. In data gathering, it employs library research by mining data from online news channels. In the data analysis, it utilizes the modern platform of NVivo 14 mainly word frequency query. To measure the campaign strategy of PAN, this article applies four indicators of marketing-mix theory: product, price, place, promotion (4P). The finding reveals that in terms of product, PAN promotes a platform of “helping people” with its past record as the reformist party and supported by the legislative candidates’ background of entrepreneurs and artists-celebrities. Regarding the price, the PAN’s campaign budget spent at least 223 billion IDR with its successful campaigns which conducted by each legislative candidate. PAN prefers to rely on the popularity of President of Joko Widodo and legislative candidates. In the context of place, the strategy of local network and canvassing are based on the creativity of each legislative candidates in attracting voters’ sympathy. The leader tour is conducted by visiting influential public figures. Concerning promotion, the campaign publication of PAN relies on printed mass media, television, and social media while event publication is carried out in various regions across the country. Among those four indicators, the price has the most significant impact which causes to the successful campaign of PAN in the 2024 Simultaneous Election.